Emergent stability in a large, free‐flowing watershed. Issue 2 (1st February 2015) - Moore, Jonathan W.; Beakes, Michael P.; Nesbitt, Holly K.; Yeakel, Justin D.; Patterson, David A.; Thompson, Lisa A.; Phillis, Corey C.; Braun, Douglas C.; Favaro, Corinna; Scott, David; Carr-Harris, Charmaine; Atlas, William I.
Abstract : While it is widely recognized that financial stock portfolios can be stabilized through diverse investments, it is also possible that certain habitats can function as natural portfolios that stabilize ecosystem processes. Here we propose and examine the hypothesis that free‐flowing river networks act as such portfolios and confer stability through their integration of upstream geological, hydrological, and biological diversity. We compiled a spatially (142 sites) and temporally (1980–present) extensive data set on fisheries, water flows, and temperatures, from sites within one of the largest watersheds in the world that remains without dams on its mainstem, the Fraser River, British Columbia, Canada. We found that larger catchments had more stable fisheries catches, water flows, and water temperatures than smaller catchments. These data provide evidence that free‐flowing river networks function as hierarchically nested portfolios with stability as an emergent property. Thus, free‐flowing river networks can represent a natural system for buffering variation and extreme events.